Cognitive performance is associated with cerebral oxygenation and peripheral oxygen saturation, but not plasma catecholamines, during graded normobaric hypoxia. Issue 9 (17th July 2019) - Williams, Thomas B.; Corbett, Jo; McMorris, Terry; Young, John S.; Dicks, Matt; Ando, Soichi; Thelwell, Richard C.; Tipton, Michael J.; Costello, Joseph T.
Abstract : New Findings: What is the central question of this study? What are the mechanisms responsible for the decline in cognitive performance following exposure to acute normobaric hypoxia? What are the main findings and their importance? We found that (1) performance of a complex central executive task ( n ‐back) was reduced at F I O 2 0.12; (2) there was a strong correlation between performance of the n ‐back task and reductions in S p O 2 and cerebral oxygenation; and (3) plasma adrenaline, noradrenaline, cortisol and copeptin were not correlated with cognitive performance. Abstract: It is well established that hypoxia impairs cognitive function; however, the physiological mechanisms responsible for these effects have received relatively little attention. This study examined the effects of graded reductions in fraction of inspired oxygen ( F I O 2 ) on oxygen saturation ( S p O 2 ), cerebral oxygenation, cardiorespiratory variables, activity of the sympathoadrenal system (adrenaline, noradrenaline) and hypothalamic–pituitary–adrenal axis (cortisol, copeptin), and cognitive performance. Twelve healthy males [mean (SD), age: 22 (4) years, height: 178 (5) cm, mass: 75 (9) kg, FEV1 /FVC ratio: 85 (5)%] completed a four‐task battery of cognitive tests to examine inhibition, selective attention (Eriksen flanker), executive function ( n ‐back) and simple and choice reaction time (Deary–Liewald). Tests were completed before and following 60 min of exposure to F I O 2 0.2093, 0.17, 0.145 and 0.12. Following 60 min of exposure, response accuracy in the n ‐back task was significantly reduced in F I O 2 0.12 compared to baseline [82 (9) vs . 93 (5)%; P < 0.001] and compared to all other conditions at the same time point [ F I O 2 0.2093: 92 (3)%; F I O 2 0.17: 91 (6)%; F I O 2 0.145: 85 (10)%; F I O 2 12: 82 (9)%; all P < 0.05]. The performance of the other tasks was maintained. Δaccuracy and Δreaction time of the n ‐back task was correlated with both Δ S p O 2 [ r (9) = 0.66, P < 0.001 and r (9) = −0.36, P = 0.037, respectively] and Δcerebral oxygenation [ r (7) = 0.55, P < 0.001 and r (7) = −0.38, P = 0.045, respectively]. Plasma adrenaline, noradrenaline, cortisol and copeptin were not significantly elevated in any condition or correlated with any of the tests of cognitive performance. These findings suggest that reductions in peripheral oxygen saturation and cerebral oxygenation, and not increased activity of the sympathoadrenal system and hypothalamic–pituitary–adrenal axis, as previously speculated, are responsible for a decrease in cognitive performance during normobaric hypoxia. Abstract :